SPE Americas Unconventional Resources Conference 2012
DOI: 10.2118/155614-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Data Analysis in Unconventional Reservoirs with Rate-Normalized Pressure (RNP): Theory, Methodology, and Applications

Abstract: Unconventional reservoirs, shale gas and oil for instance, have proven to be an important contributor to hydrocarbon production in North America. Horizontal wells with multiple transverse fractures unlocked these unconventional resources by attaining profitable production rates and increasing gas reserves for future years. A critical challenge in these types of reservoirs is characterizing the stimulated reservoir volume (SRV), by estimating the effective productive volume created during stimulation and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Classical hydraulic fracture fluid flow theory looks at fractures as single planar entities, mostly as a simplifying assumption to enable derivation of fluid flow principles (Economides et al 2013;Lee et al 2003). Planar models certainly seem too good (or simple) to be true, but many authors have shown that planar models provide a foundation for useful production analysis in unconventional reservoirs (Bello and Wattenbarger 2010;Chen and Rajagopal 1997;Samandarli et al 2012;Wattenbarger et al 1998). That said, it would be naïve to assume that fractures simply follow a planar bi-wing geometry in the presence of variable stress fields, anisotropic and heterogeneous rock properties, and natural fractures.…”
Section: Fracture Network Geometrymentioning
confidence: 99%
“…Classical hydraulic fracture fluid flow theory looks at fractures as single planar entities, mostly as a simplifying assumption to enable derivation of fluid flow principles (Economides et al 2013;Lee et al 2003). Planar models certainly seem too good (or simple) to be true, but many authors have shown that planar models provide a foundation for useful production analysis in unconventional reservoirs (Bello and Wattenbarger 2010;Chen and Rajagopal 1997;Samandarli et al 2012;Wattenbarger et al 1998). That said, it would be naïve to assume that fractures simply follow a planar bi-wing geometry in the presence of variable stress fields, anisotropic and heterogeneous rock properties, and natural fractures.…”
Section: Fracture Network Geometrymentioning
confidence: 99%
“…One method that has proved to be very powerful is rate-normalized pressure (RNP) and RNP 0 (semilog derivative of RNP with respect to material balance time or pseudo-time) analysis which has been used in recent years for analyzing production data from multi-fractured horizontal wells Samandarli et al, 2012). Analogous to classic well-test analysis, RNP, which is the inverse of PNR, and RNP 0 are used to analyze production data.…”
Section: Gasmentioning
confidence: 99%
“…The most common methods for fracture characterization are rate-transient analysis (RTA), pressure-transient analysis (PTA), micro-seismic analysis, and tracer test. Many researchers used RTA and PTA to characterize the fracture network because production data are available for almost every well. Micro-seismic monitoring is also broadly used in the field to characterize the fracture network during and after the hydraulic fracturing operations. Tracer test is another method commonly used to characterize the fracture network. Each of these three methods has its strengths and limitations.…”
Section: Introductionmentioning
confidence: 99%